A statistical quality control study on Philippine Batteries Inc. - Diaz, Maria Regina (College of Engineering, 2005)
Philippine Batteries Inc. (PBI), under RAMCAR Group of Companies, is a leading manufacturer of lead-acid batteries for cars, trucks, motorcycles and other industrial applications. The company?s aimed towards producing goods and providing services that will generate consumer satisfaction in terms of quality, costs and delivery. The study is concerned with the maintaining or improving process control as well as reducing variability. The proponents were assigned on three areas of production; namely, continuous properzi where lead strips are produced, the plates area where the plates are formed, and the assembly section where parts are put together to form a battery. In the continuous properzi section, the proponents were assigned to analyze tensile strength and percent elongation test results to determine the capability of the strip casting process to produce strips that meet specifications. The head of the quality assurance laboratory also wanted to determine existing relationships among different traits and properties of strips such as thickness, tensile strength and percent elongation prior to fracture.